IMPLEMENTASI SISTEM PPDB ZONASI DALAM PERSPEKTIF HAK KONSTITUSIONAL ATAS PENDIDIKAN DI INDONESIA - Putri, Kesha Alifia; Trisiana, Anita; Prasetyo, Agus; Amrullah, Amrullah; Spetiarko, Angga; Narendra, Muhammad Alvin (STKIP Pesisir Selatan, 2025)
This article examines the implementation of the zoned-based New Student Admission (PPDB) system in relation to the fulfillment of citizens' rights to fair and equitable education in Indonesia. The study focuses on the execution of zoning policies by the Surakarta City Education Office and the perceptions of schools regarding the effectiveness of this system. The research method used is a qualitative approach through in-depth interviews; this study analyzes how zoning policies are technically implemented, the extent to which the community responds to the implementation, and how the relevant parties assess its impact on access to education, especially for prospective students from peripheral areas. The research results show that 63.3% of the majority of respondents stated that the zoning system is in accordance with the principles of justice as stipulated in the 1945 Constitution of the Republic of Indonesia, although in principle, zoning is intended for equity, its implementation still faces challenges, such as disparities in facilities between schools, limited capacity, and uneven distribution of education quality. In this regard, the author highlights the importance of continuous evaluation and improvement of policies so that their implementation does not hinder the public's right to access equal and quality education services.